Legal Reformulation on Expired Provisions of Prosecution of Tax Crimes in Indonesia - Situmorang, Parulian (Scientia Integritas Utama, 2023)
There are still philosophical gaps and juridical gaps in terms of the formation and implementation of Article 40 of the Law on General Provisions and Tax Procedures in Indonesia (KUP Law). Those gaps show the need for ideal regulation of the expiry date for prosecuting criminal offenses in the field of taxation in Indonesia in the future. Based on normative juridical methods using secondary data in the form of primary, secondary and tertiary legal materials, this study produces two conclusions. First, the expiry date for prosecuting criminal acts in the field of taxation currently in force in Indonesia has legal uncertainty due to explanations that do not interpret prosecution correctly. Apart from that, there are other criminal provisions in the field of taxation which are not related to